Emotions and decision-making in boardrooms—a systematic review from behavioral strategy perspective - Hasson Marques, Rosine; Violant-Holz, Veronica; Damião da Silva, Eduardo (Frontiers in Psychology, 2024)
This systematic review examines the influence of emotions on strategic decision-making in business context, from the perspective of behavioral strategy. We examined 1,227 articles from two databases (Web of Science and PsycInfo), and after applying the inclusion and exclusion criteria, the final sample resulted in 43 articles. Our systematic review focuses on the role of emotions in strategic decision-making as well as the decision-making process itself. This systematic review explores research using a variety of approaches and a combination of theoretical and empirical perspectives brought by the literature. It aims to address three main questions: how board members’ emotions influence their decision-making; what insights behavioral strategy provides on the emotional aspect of strategic decision-making; and what are the main theories linking emotions to strategic decision-making in the business context. The results demonstrate how emotions can affect the quality of decisions and imply that conflict resolution and emotional intelligence are relevant skills for making strategic decisions. This analysis supports the need for incorporating emotional insights into strategic planning methods by considering agreeable and divergent points of view.